1997
DOI: 10.1247/csf.22.239
|View full text |Cite
|
Sign up to set email alerts
|

Association of hnRNP S1 Proteins C2 and D2 with Vimentin Intermediate Filaments.

Abstract: Keywords: S I protein/hnRNP/intermediate filament/microtubule/micro filament/vimentin ABSTRACT. SI proteins A-D are hnRNPproteins which were originally isolated from cell nuclei of various tissues, by selective extraction at pH 4.9 from the supernatants of nuclei mildly treated with DNase I or RNase A. In the present study, a hybridoma was isolated which produced a monoclonal antibody that reacted specifically with SI proteins C2 and D2. Whenthe antibody was used in indirect immunofluorescence staining of cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…A hybridoma producing monoclonal antibody McAb 351, which is highly specific for S1 proteins C2 and D2, has been isolated. Cell staining with this antibody showed that they occur not only in the nucleus but also in the cytoplasm often in association with VFs in cultured cells (Tsugawa et al, 1997). In this study, we verified the association of S1 proteins with VFs, and investigated its biological significance.…”
Section: Introductionsupporting
confidence: 51%
See 4 more Smart Citations
“…A hybridoma producing monoclonal antibody McAb 351, which is highly specific for S1 proteins C2 and D2, has been isolated. Cell staining with this antibody showed that they occur not only in the nucleus but also in the cytoplasm often in association with VFs in cultured cells (Tsugawa et al, 1997). In this study, we verified the association of S1 proteins with VFs, and investigated its biological significance.…”
Section: Introductionsupporting
confidence: 51%
“…Indirect immunofluorescence staining with antibody McAb 351, specific for S1 proteins C2 and D2, shows localization of these proteins on vimentin filaments (VFs) as well as in the nuclei of VF-containing cells such as HaK cells and HeLa cells (Tsugawa et al, 1997). S1 proteins on VFs (S1 fibers) were similarly observed in ARL rat liver epithelial cells (Fig.…”
Section: Localization Of S1 Proteins On Vfsmentioning
confidence: 76%
See 3 more Smart Citations